METHOD OF INCREASING THE EFFICIENCY OF COMPETITIVE ACTIVITIES OF HIGH-LEVEL FEMALE VOLLEYBALL PLAYERS - Ruzmetov Azizbek Tangirberganovich («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article, based on the conducted research, examines the process of preparing the setters of the women’s volleyball team of Urgench State University for competitions to organize eﬀective combination actions of volleyball players.